Wear behavior of WC-Ni sliding against graphite under water lubrication. Issue 11 (November 2017) - Zhang, Gaolong; Liu, Ying; Wang, Yuechang; Guo, Fei; Liu, Xiangfeng; Wang, Yuming
Abstract: Wear of hard materials in contact with softer materials is a neglected area of research. However, we observed considerable wear phenomenon at a hard WC-Ni surface sliding over soft graphite under water lubrication. The influences of applied load and the application history on the wear of surface were addressed in our experimental design. Wear of both graphite and WC-Ni surfaces increased with a greater applied load and repeated sliding. The topographies of the worn surfaces showed clear micro-scratches on the hard WC-Ni surface. Scanning electron microscopy and X-ray photoelectron spectroscopy analyses revealed that the abrasive wear of the WC-Ni surface could be attributed to hard WC particles embedded in the graphite surface. These hard particles were formed by shearing of sharp WC-Ni asperities under certain conditions and intrinsic defects of the WC-Ni surface could accelerate this wear process.